Trustworthy public randomness with sloth, unicorn, and trx. (2017) - Lenstra, Arjen K.; Wesolowski, Benjamin
Many applications require trustworthy generation of public random numbers. It is shown how this can be achieved using a hash function that is timed to be as slow as desired ( sloth ), while the correctness of the resulting hash can be verified quickly. It is shown how sloth can be used for uncontestable random number generation ( unicorn ), and how unicorn can be used for a new trustworthy random elliptic curves service ( trx ) and random-sample voting.